Investigation on the surface properties of chemically modified natural fibers using inverse gas chromatography - Cordeiro, Nereida (2021)
This paper presents the application of inverse gas chromatography (IGC) technique for characterization and comparison of the surface properties of the natural fibers as reinforcement fillers in wood plas tic composites. The effects of chemical modification using 1% NaOH were also studied. The fibers used for this work were Iranian cultivated eucalyptus, spruce, bagasse, and wheat straw. Chemical composi tion of fibers was found to be modified after treatment as characterized by Fourier transform infrared spectroscopy (FTIR). The crystallinity of fibers and the specific interaction was improved by the alkaline treatment, with more relevance to the agro-fibers. The IGC shows also a general increase in the wettability of the modified fiber when compared with the raw (unmodified) samples. Alkaline treatment achieves the best overall improvement in the properties evaluated of the agro-fibers when compared to the wood fibers.